Priority 4: Sustainable development of rural communities in Mediterranean Region - Lamberti L.; Belsanti V.; Woodgate G.; Bessaoud O. (Feeding knowledge, 2017)
The present document aims to provide a framework for further discussions and investigation on how sustainable development of small rural communities in SEMC can contribute to food security, which can guide future policy design to better target the needs of those communities for supporting and promoting development process. The specific objectives of this paper are to present the situation of small rural communities in the SEMC taking into consideration their geographical and social context, their farming systems, livelihoods strategies, political and institutional context, environmental, social and economic challenges, and what are the aspects that need additional research to provide a more target specific set of policies to address development and respond to the need of guaranteeing food security.
Expo Milano 2015